Workshop on Graph Labelling in Theory and Applications for Prospective Mathematics Teachers - Rikayanti Rikayanti; Karunia Eka Lestari; Aditya Prihandhika; Mokhammad Ridwan Yudhanegara (AN-NAS: Jurnal Pengabdian Masyarakat, 2026)
Thinking is the process of the mind processing information, in a mathematical context it can be expressed as the process of the mind reasoning systematically and logically in an effort to draw a conclusion from a phenomenon. The relationship between phenomena can be represented using the concept of graphs. Through this workshop, participants are invited to interpret the relationships between phenomena using graphs. The topic of labelling was chosen to deepen the understanding in applying mathematical concepts. After this activity, it is expected that the participants will be able to analyse problems that can be solved using graph concepts. Most of the participants are mathematics education students, mathematics teachers, and researchers in the field of discrete mathematics (specifically graphs). This activity demonstrates the participants' interest in graph concepts and their applications in the field of education.